2022
DOI: 10.3390/ijms23158696
|View full text |Cite
|
Sign up to set email alerts
|

Gene Variants Related to Cardiovascular and Pulmonary Diseases May Correlate with Severe Outcome of COVID-19

Abstract: Background: Severe outcomes of COVID-19 account for up to 15% of all cases. The study aims to check if any gene variants related to cardiovascular (CVD) and pulmonary diseases (PD) are correlated with a severe outcome of COVID-19 in a Polish cohort of COVID-19 patients. Methods: In this study, a subset of 747 samples from unrelated individuals collected across Poland in 2020 and 2021 was used and whole-genome sequencing was performed. Results: The GWAS analysis of SNPs and short indels located in genes related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The review of variations across mitochondrial DNA (mtDNA), conducted by Wu et al [8] points to differences in ND1, ND2, ND3 genes and in the D-loop region as related to an increased risk of severe COVID-19. Moreover, it was demonstrated that several gene variants related to cardiovascular and pulmonary diseases were correlated with the severe outcome of COVID-19 [9].…”
Section: Introductionmentioning
confidence: 99%
“…The review of variations across mitochondrial DNA (mtDNA), conducted by Wu et al [8] points to differences in ND1, ND2, ND3 genes and in the D-loop region as related to an increased risk of severe COVID-19. Moreover, it was demonstrated that several gene variants related to cardiovascular and pulmonary diseases were correlated with the severe outcome of COVID-19 [9].…”
Section: Introductionmentioning
confidence: 99%